Vaccination coverage rates and attitudes towards mandatory vaccinations among healthcare personnel in tertiary-care hospitals in Greece. (3rd June 2022) - Maltezou, Helena C.; Tseroni, Maria; Drositis, Ioannis; Gamaletsou, Maria N.; Koukou, Dimitra Maria; Bolikas, Emmanouil; Peskelidou, Emmanuela; Daflos, Charalambos; Panagiotaki, Evangelia; Ledda, Caterina; Pavli, Androula; Moussas, Nikolaos; et al.
ABSTRACT: Objectives: Our aim was to estimate vaccination and susceptibility rates against vaccine-preventable diseases among healthcare personnel (HCP) in eight hospitals. Methods: Cross-sectional survey. Results: A total of 1284 HCP participated (physicians: 31.3%, nursing personnel: 36.6%, paramedical personnel: 11.1%, administrative personnel: 13.2%, supportive personnel: 7.3%). Vaccination rates were 32.9% against measles and mumps, 38.1% against rubella, 5.7% against varicella, 9.2% against hepatitis A, 65.8% against hepatitis B, 31.8% against tetanus-diphtheria, 7.1% against pertussis, 60.2% against influenza, and 80.1% against COVID-19. Susceptibility rates were as follows: 27.8% for measles, 39.6% for mumps, 33.4% for rubella, 22.2% for varicella, 86.3% for hepatitis A, 34.2% for hepatitis B, 68.2% for tetanus-diphtheria, and 92.9% for pertussis. Older HCP had higher susceptibility rates against mumps, rubella, varicella, hepatitis A, hepatitis B, tetanus-diphtheria, and pertussis (p-values <0.001 for all). Mandatory vaccinations were supported by 81.85% of HCP. Conclusions: Although most HCPs supported mandatory vaccinations, significant vaccination gaps, and susceptibility rates were recorded. The proportion of susceptible HCP to measles, mumps, rubella, and varicella has increased in the past decade, mostly because of reduction in acquired cases of natural illness. Vaccination programs for HCP should be developed. A national registry to follow HCP's vaccination rates is urgently needed.